Indigenous livestock as the backbone of African animal agriculture: The importance of adaptive attributes and potential for their exploitation - Rege, J.E.O. (1994)
Africa is well endowed with a diversity of breeds and strains of livestock, which have proved remarkably suited to survive and produce under prevailing environmental rigours. Over 90 percent of the ruminant population in Africa is indigenous, although the numbers of distinct breeds of cattle, sheep and goat is not known. The indigenous African cattle posses unique adaptive attributes: the zebu and their derivatives are tolerant to climatic stresses, especially to heat; they have genetic adaptation to thrive on poor quality forages, and they have some resistance to pests and diseases. Their productive performance in terms of milk quality and calf weaning weight per cow, are superior to those of European breeds under these environments. The improvement of African animal agriculture depends on the utilization of indigenous animal genetic resources. If crossbreeding is opted for, it is important that a programme of evaluation, improvement and conservation of the indigenous parental breeds be maintained in parallel.